Cities of Migration Understanding the diversity of urban diversities in Europe - Pisarevskaya, Asya.; Scholten, Peter; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book develops a typology of cities by exploring how current levels of migration-related diversity and segregation relate to three groups of factors: international mobilities, inequalities and political-institutional aspects of local governance. Based on both quantitative and qualitative data from 16 cities in four European countries (France, Germany, The Netherlands, and Italy), the book compares the cities and uses a method of fuzzy-set Qualitative Comparative Analysis. It demonstrates the shared contingencies of factors among the cities within each type and the crucial differences between the types of localities, and offers a more differentiated, holistic understanding of migration-related diversity configurations through the five conceptualised types: (1) Superdiverse cities, (2) Postindustrial diverse cities. (3) Middle class diverse cities, (4) Divided cities, and (5) Marginal migration cities. As such, the book is a valuable read to all those who would like to learn more about urban migration-related diversity and how it is formed and governed.
1. Introduction -- 2. Conceptualizing the Plurality of Urban Diversities -- 3. Mapping the Diversity of Urban Diversities -- 4. Cities Cluster I: High Diversity and Low Segregation -- 5. Cities Cluster II: High Diversity And High Segregation -- 6. Cities Cluster III: Low Diversity and High Segregation -- 7. Cities Cluster IV: Low Diversity and Low Segregation -- 8. Towards a Typology of Urban Diversities -- 9. Conclusions -- References.
Keywords: Emigration and immigration; Emigration and immigration -- Government policy; Human geography; Emigration and immigration -- Social aspects; Human Migration; Migration Policy; Human Geography; Sociology of Migration